Testing software and systems : 27th IFIP WG 6.1 International Conference, ICTSS 2015, Sharjah and Dubai, United Arab Emirates, November 23-25, 2015 : proceedings /: 27th IFIP WG 6.1 International Conference, ICTSS 2015, Sharjah and Dubai, United Arab Emirates, November 23-25, 2015 : proceedings. (2015) - Unknown
No abstract available